AUDIT-ABLE PROCUREMENT PROCESS WITH CLOUD COMPUTING BLOCKCHAIN - Heshaful Bahri, Khairiena Humaira (IRC, 2019)
From raw materials to distribution to after-sale support, understanding the location and flow of products within your supply chain is critical and not only for maximizing efficiency. Transparency in the supply chain is one of the most important and difficult areas for enhancing logistics and supply chain management. Consumers demand transparency on where and how products are made. Distrust between organizations has historically discouraged them from sharing or relying on shared data. The smart contract is the key component of the blockchain, which has rendered blockchain beyond the reach of cryptocurrency and accessible to a variety of applications such as banking, IoT, supply chain, electronic identification, business process management and more. And with digital supply chain, integration has become complex. In this paper, it explains how the blockchain will contribute to the procurement process because of the characteristics possessed. Characterized as an open-source, decentralized, distributed transaction data storage database. This technology enables two sides to transact directly using duplicate, connected ledgers called blockchains instead of relying on centralized intermediaries. This makes transactions significantly more transparent than centralized systems ' operations. As a consequence, transactions are performed on the basis of network agreement without depending on explicit confidence, but on distributed confidence. There are many opportunities to use this technology to enhance the transparency of the supply chain management. Blockchain technology has the potential to transform how businesses are organized and managed. It allows companies to eliminate transaction costs and use outside resources as easily as internal resources.